The Effect of Number Pocket Media on Students’ Learning Interest and Conceptual Understanding of Multiplication in Third-Grade Elementary School - Hellen Rizky Amelia; Muhamad Sofian Hadi (Faculty of Teacher Training and Education, 2025)
Mathematics is a fundamental subject in elementary school that plays an important role in developing students’ logical, systematic, and critical thinking skills. However, many lower-grade students still experience difficulties in understanding multiplication concepts because learning activities tend to focus on memorizing multiplication tables. This condition leads to low learning interest and weak conceptual understanding. This study aims to analyze the effect of number pocket media on improving learning interest and conceptual understanding of multiplication among third-grade students. The research employed a quantitative method with a pre-experimental one-group pretest–posttest design. The subjects consisted of 27 third-grade students of SD Taruna Mandiri. Research instruments included an achievement test to measure conceptual understanding and a Likert-scale questionnaire to assess students’ learning interest. Data were analyzed using descriptive statistics and the Wilcoxon Signed Rank Test. The results showed that the average score increased from 48.89 in the pretest to 67.41 in the posttest, with mastery learning percentages rising from 37.04% to 70.37%. The Wilcoxon test yielded a significance value of 0.000 < 0.05, indicating a significant difference. In addition, the learning interest questionnaire scores increased from 2.61 to 3.67 after the implementation of the learning media. Therefore, number pocket media are proven to be effective in improving students’ learning interest and conceptual understanding of multiplication. Teachers are encouraged to use this simple concrete media as an innovative instructional strategy to make mathematics learning more interactive and enjoyable.